2012
DOI: 10.3748/wjg.v18.i32.4278
|View full text |Cite
|
Sign up to set email alerts
|

Use of butyrate or glutamine in enema solution reduces inflammation and fibrosis in experimental diversion colitis

Abstract: The improvement of experimental diversion colitis following glutamine or butyrate enemas highlights the importance of specific luminal nutrients in the homeostasis of the colonic mucosa and supports their utilization for the treatment of human diversion colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 45 publications
4
46
0
7
Order By: Relevance
“…Initial trials in humans demonstrated that butyrate enemas for 2–6 weeks were able to treat patients with diversion colitis,[26] suggesting that diversion colitis may be the result of an absence of the metabolically vital SCFAs. While a follow-up trial f only 2 weeks of treatment did not recapitulate the results of the initial study[27], more recent studies in rats did replicate the initial findings[28]. In the treatment of ulcerative colitis (UC), butyrate enemas have showed some promise in a subset of patients.…”
Section: Non-digestible Polysaccharides (Butyrate Production)mentioning
confidence: 99%
“…Initial trials in humans demonstrated that butyrate enemas for 2–6 weeks were able to treat patients with diversion colitis,[26] suggesting that diversion colitis may be the result of an absence of the metabolically vital SCFAs. While a follow-up trial f only 2 weeks of treatment did not recapitulate the results of the initial study[27], more recent studies in rats did replicate the initial findings[28]. In the treatment of ulcerative colitis (UC), butyrate enemas have showed some promise in a subset of patients.…”
Section: Non-digestible Polysaccharides (Butyrate Production)mentioning
confidence: 99%
“…The application of enemas containing natural or synthetic substances, with antioxidant effects or rich SCFA solutions, improves tissue inflammatory changes detected in the DC model [10][11][12][13][14] . Conversely, the exposure of the colonic mucosa to substances with great oxidant power, such as hydrogen peroxide (H 2 O 2 ), worsens the epithelial damage 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms for the development of diversion colitis have been proposed, including a nutritional deficiency of SCFA in the colonic lumen [101, 102]. Studies in Wistar rats suggest that the use of SCFA enemas may improve symptoms [102, 103]. Harig et al [101] successfully treated patients with diversion colitis using SCFA enemas.…”
Section: Disease States Linked With Scfasmentioning
confidence: 99%